3x + 4y = 19
3x - 2y = 1
equação do 1 grau modo da substituição
Soluções para a tarefa
Respondido por
2
3x = 19 - 4y
(substituindo)
19 - 4y - 2y = 1
-4y - 2y = 1 - 19
-6y = -18 .(-1)
6y = 18
y = 18 / 6
y = 3
(substituindo novamente)
3x + 4.3 = 19
3x + 12 = 19
3x = 19 - 12
3x = 7
x = 7/3
x = 2,3 (aproximadamente)
(substituindo)
19 - 4y - 2y = 1
-4y - 2y = 1 - 19
-6y = -18 .(-1)
6y = 18
y = 18 / 6
y = 3
(substituindo novamente)
3x + 4.3 = 19
3x + 12 = 19
3x = 19 - 12
3x = 7
x = 7/3
x = 2,3 (aproximadamente)
matheus101:
fez**
Perguntas interessantes
Matemática,
1 ano atrás
História,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás
Português,
1 ano atrás